The Effectiveness of Returning Assets Resulting from Corruption Crimes After Court Decisions - Ronald Hasudungan Sianturi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Asset return is a vital pillar in the eradication of profit-oriented corruption crimes, but executions after court decisions often fail to restore the state's finances significantly. This study examines the effectiveness of the return of assets resulting from corruption crimes after court decisions in Indonesia using normative-empirical legal research methods through normative and sociological juridical approaches. The results of the study show that the effectiveness of asset returns is still very low, where in 2022 the rate of return of state losses through additional penalties for compensation only reached 7.83% of the total losses which reached Rp48.786 trillion. The low recovery is caused by three main factors, namely structural constraints such as limited number of prosecutors and budget, juridical constraints in the form of unclear asset tracking authority and replacement confinement loopholes in Article 18, and technical obstacles such as poor inter-institutional coordination and limited access to banking data. The conviction-based forfeiture system currently adopted has proven to be ineffective because it gives time for the perpetrator to hide or transfer assets before the inkracht verdict. This study recommends urgent legal reform through the adoption of non-conviction based forfeiture and the application of the concept of Criminal Execution Investigation to accelerate the recovery of state losses, but must still be balanced with strong human rights protection and due process of law.